ANNOTATED TRANSLATION OF SEVEN ARTISTS’ SONG LYRICS - Ferinda Nisrina Machmud; Evert Haryanto Hilman (Asosiasi dosen IDEBAHASA KEPRI, 2022)
The aimed of this research is to get a perfect translation so the translated text effortlessly understood through the reader. the object of this research is selected from 7 artists’ songs by Pauline Scott, Jocelvn, Billie Eilish, Bruno Major, Bruno Mars, and Role Model. This research focused on two types of figurative language which are idioms and metaphors. This research belongs to the area of analysis of the source text and the translated text, which covers a study on annotated translation using introspective and retrospective methods since the aim of this research is to get a perfect translation so the translated text effortlessly understood through the readers, also this research used translation strategies by Chesterman's (2016) theory and also other support theories which only focused on syntactic and semantic strategies to analysed the translation strategies of figurative language in selected song lyrics. The result of this research found that trope change is the most common semantic strategy used when analysed the data, while the scheme change is the most frequent syntactic strategies used in these song lyrics.